Design and Validation of Transversal Competences Assessment Instrument (TCAI) in Compulsory Secondary Education - Lourdes Villardón-Gallego; Lara Yáñez-Marquina; Lirio Flores-Moncada; Virginia Ros-Vitorica (Universidad de Navarra, 2022)
The basic competences (such as Information Acquisition and Management; Understanding and Expression of Information and Emotions; Competence to Do and Undertake; Competence to Live Together; and Competence to Be) are necessary to achieve adequate personal, social and professional development. This study develops and validates, through Confirmatory Factor Analysis, an instrument for assessing them. Data were collected from 751 secondary students, with ages ranging from 11 to 18. The results confirm the structure of the instrument, comprising five independent scales. The instrument is valid for its application, either as a whole or separately.